CHRISTIAN RELIGIOUS EDUCATION MANAGEMENT, GOVERNMENT SERVICE, IN CELL GROUPS ON THE QUALITY OF THE FAITH OF CHURCH MEMBERS IN INDONESIA BETHEL CHURCH OF GRAHA PENA - Imron Widjaja; Lasmaria Nami Simanungkalit (Scriptura Indonesia, 2020)
This study examines the management of christian religious education as one form of shepherding service formation in cell groups in maturing, guiding and directing to apply the word of God. Christian religious education management as a model and example in the formation of church pastors in reaching sinners for Christ. This research was conducted at GBI Graha Pena with a total sample of 88 people who were active in participating in cell groups. The results of this study indicate that educational services are good that have led to pastoral care in realizing the Quality of Faith of GBI Graha Pena congregation members to reach people who do not yet believe in Christ. The effectiveness of the implementation of pastoral services that lead to the tasks and objectives of the church's mission through cell groups seen from members of cell groups who see the effectiveness of the service is supported by effectiveness: 58 respondents visitation (65.9%), help of sick people 88 respondents (100%), prayer of release 88 respondents (100%), service grief 88 respondents (100%).